Síntese, caracterização e estudo termoanalítico dos mandelatos de lantanídeos(III), exceto o promécio, e de ítrio(III) no estado sólido - Gigante, Andréa Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the present work, the compounds Ln(L)3nH2O – where Ln represents trivalent lanthanide (La to Lu, except promethium) and yttrium(III) ions and L is mandelate (C6H5CH(OH)CO2 -)) – have been synthesized. The compounds were synthesized by stoichiometric addition of the sodium mandelate ligand to the respective solutions of chloride or nitrate lanthanides and yttrium, slowly with stirring. The formation of the lanthanum to neodymium compounds occurred after maintaining the solutions under ebullition for 30 minutes. After filtration, due to a great loss during the washing of these precipitates, small quantity of these mandelates were obtained. Thus, the same were also prepared by neutralization of the respective lanthanide carbonates with mandelic acid in slight excesso. The characterization of these compounds in solid state was performed using the following techniques: complexometry; X-ray powder diffractometry; infrared spectroscopy; simultaneous thermogravimetry and differential thermal analysis (TG–DTA); thermogravimetry and derivative thermogravimetry (TG/DTG); simultaneous thermogravimetry and differential scanning calorimetry coupled to absorption spectroscopy in the infrared region with Fourier transform (TG-DSC / FTIR) and differential scanning calorimetry (DSC). These techniques provided information about stoichiometry, dehydration, coordination sites, thermal behavior, composition and structure of synthesized compounds. From TG curves and complexometry results, a general formula could be established for these compounds in the solid state. The X-ray powder patterns pointed out that the synthesized compounds have a low crystalline structure and evidence concerning the formation of isomorphous series. The infrared spectroscopy data suggest that the mandelate ion acts as a chelating bidentate ligand towards the metal ions considered in this work, with a prominently ionic character. The TG–DTA and DSC curves provided...

No presente trabalho foram sintetizados em solução aquosa os compostos Ln(L)3nH2O – onde Ln representa os íons lantanídeos trivalentes (La ao Lu, exceto o promécio) e o ítrio(III) e L representa o íon mandelato (C6H5CH(OH)CO2 -)). Os compostos foram sintetizados por lenta adição de quantidades estequiométricas do ligante mandelato de sódio nas respectivas soluções de cloretos ou nitratos de lantanídeos e de ítrio, sob agitação contínua. A formação dos compostos de lantânio ao neodímio foi verificada após a manutenção das soluções em ebulição durante 30 minutos. Após a sua filtração, observou-se grande perda por solubilidade destes compostos durante a lavagem dos seus precipitados, sendo obtidas apenas pequenas quantidades dos mesmos. Devido a isso, foi realizada nova preparação destes compostos por meio da reação dos seus respectivos carbonatos com o ácido mandélico em ligeiro excesso. Já para os compostos de samário ao lutécio e ítrio a precipitação ocorreu de forma instantânea assim que se adicionou o ligante aos cloretos dos respectivos íons metálicos. A caracterização dos compostos no estado sólido foi realizada através da utilização das seguintes técnicas: complexometria; difratometria de raios X pelo método do pó; espectroscopia de reflectância total atenuada na região do infravermelho; termogravimetria e análise térmica diferencial simultâneas (TG–DTA); termogravimetria e termogravimetria derivada (TG/DTG); termogravimetria e calorimetria exploratória diferencial simultâneas acopladas à espectroscopia de absorção na região do infravermelho com transformada de Fourier (TG-DSC/FTIR) e calorimetria exploratória diferencial (DSC). Estas técnicas forneceram informações sobre a estequiometria, a desidratação, os sítios de coordenação, o comportamento térmico, composição e estrutura dos compostos sintetizados. Com os resultados obtidos pelas curvas TG e pela...
Keywords: Quimica analitica; Metais de terras raras; Análise espectral; Itrio; Yttrium